2012
DOI: 10.1029/2011ja017268
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER orbital observations of large‐amplitude Kelvin‐Helmholtz waves at Mercury's magnetopause

Abstract: [1] We present a survey of Kelvin-Helmholtz (KH) waves at Mercury's magnetopause during MESSENGER's first Mercury year in orbit. The waves were identified on the basis of the well-established sawtooth wave signatures that are associated with nonlinear KH vortices at the magnetopause. MESSENGER frequently observed such KH waves in the dayside region of the magnetosphere where the magnetosheath flow velocity is still subsonic, which implies that instability growth rates at Mercury's magnetopause are much larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
93
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 61 publications
8
93
1
Order By: Relevance
“…This configuration where the IMF is parallel to the planetary magnetic field in the MP is favourable for the KHI along the equatorial magnetospheric flanks 16 . The 29-September and subsequent observations show a clear asymmetry in the KHI in favour of dusk 11 , which will be explained through consideration of asymmetries in the forces acting on the ions at dusk and dawn.…”
Section: Messenger Spacecraft Observations Of the Khi At Mercurymentioning
confidence: 78%
See 3 more Smart Citations
“…This configuration where the IMF is parallel to the planetary magnetic field in the MP is favourable for the KHI along the equatorial magnetospheric flanks 16 . The 29-September and subsequent observations show a clear asymmetry in the KHI in favour of dusk 11 , which will be explained through consideration of asymmetries in the forces acting on the ions at dusk and dawn.…”
Section: Messenger Spacecraft Observations Of the Khi At Mercurymentioning
confidence: 78%
“…The IMF orientation in the magnetosheath before these sawtooth oscillations varied from southward to northward 8 , but in the majority of cases where the KHI is observed the IMF is strongly northward 11 . This configuration where the IMF is parallel to the planetary magnetic field in the MP is favourable for the KHI along the equatorial magnetospheric flanks 16 .…”
Section: Messenger Spacecraft Observations Of the Khi At Mercurymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in-situ observations from Cluster, THEMIS, Geotail, Double Star, MESSENGER, and Cassini have indicated that the KHI appears capable of generating surface waves (e.g., Fairfield et al 1990;Hasegawa et al 2004;Nykyri et al 2006;Fairfield et al 2007;Volwerk et al 2007;Taylor and Lavraud 2008;Boardsen et al 2010;Masters et al 2010;Cutler et al 2011;Hwang et al 2011bHwang et al , 2012Sundberg et al 2012). KHW have also been identified in the magnetosheath (Walker et al 2011b), the solar corona (Ofman and Thompson 2011), and the ionospheres of Mars and Venus (Pope et al 2009).…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%